Defective chemoattractant-induced calcium signalling in S100A9 null neutrophils. - McNeill, E; Conway, S; Roderick, H; Bootman, MD; Hogg, N (2007)
The S100 family member S100A9 and its heterodimeric partner, S100A8, are cytosolic Ca2+ binding proteins abundantly expressed in neutrophils. To understand the role of this EF-hand-containing complex in Ca2+ signalling, neutrophils from S100A9 null mice were investigated. There was no role for the complex in buffering acute cytosolic Ca2+ elevations. However, Ca2+ responses to inflammatory agents such as chemokines MIP-2 and KC and other agonists are altered. For S100A9 null neutrophils, signalling at the level of G proteins is normal, as is release of Ca2+ from the IP(3) receptor-gated intracellular stores. However MIP-2 and FMLP signalling in S100A9 null neutrophils was less susceptible than wildtype to PLCbeta inhibition, revealing dis-regulation of the signalling pathway at this level. Downstream of PLCbeta, there was reduced intracellular Ca2+ release induced by sub-maximal levels of chemokines. Conversely the response to FMLP was uncompromised, demonstrating different regulation compared to MIP-2 stimulation. Study of the activity of PLC product DAG revealed that chemokine-induced signalling was susceptible to inhibition by elevated DAG with S100A9 null cells showing enhanced inhibition by DAG. This study defines a lesion in S100A9 null neutrophils associated with inflammatory agonist-induced IP3-mediated Ca2+ release that is manifested at the level of PLCbeta.